Estimation of Social Benefits in Cost-benefit Analysis - Fodor, Beáta (Theory, Methodology, Practice – Review of Business and Management, 2012)
While examining the cost-benefit analysis related to public policy decisions in the Hungarian and international literature, this paper is looking for the answer to the question of what the methodological principles are according to which the benefit impacts can be determined. The processed Hungarian and English-language studies indicate that the theoretical-methodological questions of the determination of benefit impacts are not clear cut. The author has constructed a model that contains the most important method-components of the benefit impact analysis. Based on six major factors, the model illustrates the analysis of the benefit impact, divided into elementary methods.